PENGARUH JUS NANAS MADU TERHADAP PENURUNAN KADAR ASAM URAT PADA PENDERITA ARTHRITIS GOUT DI WILAYAH PUSKESMAS RAJEG TAHUN 2021 - Muthia Salsa; Siti Haeriyah (Nusantara Hasana Berdikari, 2021)
Gout disease in the medical world is called gout (Arthritis Gout) which is a diseade of the joints caused by high levels of uric acid in the body. Prevalence of gout in Indonesia, sufferers of joint disease due to high uric acid occur in several provinces such as Aceh as much as 13,26%, Bengkulu as much as 12,11 %, Bali as much as 10,46 % dan Papua as much as 10,43 %. The prevalence of join disease in Banten is 6,15%, Kabupaten Tangerang is 6,52%, Kota Tangerang is 6,03%. This study was conducted to determine whether there is an effect of giving pineapple juice on reducing uric acid levels in patients with gouty arthritis in the Rajeg Health Center area in 2021. The type of research used is a quantitative study using a pre-experimental design with a one-group design. The population of this study were all gout suffers. The sampling tecnique was Cluster Sampling with a sample that collected 32 gout sufferers. Respondents were checked for uric acid levels before and after being given honey pineapple juice using the Easy Touch GCU digital tool to determine uric acid levels. Before being given honey pineapple juice therapy the respondents' average uric acid level was 8.3 mg/dl, after being given honey pineapple juice therapy the respondents' average uric acid level was 6.7 mg/dl. Based on the results of the Wilcoxon test on 32 people, there was a change in blood uric acid levels with a p-value of 0.000. The results of statistical tests show that the p value is smaller than the a value (0.05), thus Ho is rejected. This study shows that there is a therapeutic effect of giving honey pineapple juice on changes in uric acid levels. After being given honey pineapple juice there is a change in uric acid levels, so it can be expected that gout sufferers should often consume honey pineapple juice to reduce uric acid levels in the body and often do uric acid checks at least every month or if they reduce complaints and reduce food purines tall.